Exploring gender-based biological concepts: an analysis of bilingual secondary school students - Endah Kristiani; Rizhal Hendi Ristanto; Elsa Lisanti (Biosfer: Jurnal Pendidikan Biologi, 2020)
The purpose of this study was to analyze gender-based biological concepts understanding at secondary school students of bilingual programs. 6 (sixth) problems, according to Bloom's taxonomy categorization, were designed consisted of: understanding, applying, analyzing, evaluating, and creating. The topics included cell, classification of the organism, ecology, plant anatomy and physiology, and human anatomy and physiology. Samples were 47 students from grade nine (secondary school) from one of bilingual secondary schools in Jakarta, Indonesia. Data obtained were analyzed quantitatively and qualitatively. The analysis showed that the average value of the concept comprehension test was 55.07, which was below the Minimum Criteria of Completeness score of 73. The average value of male students was 57.29, and the average value of female students was 52.85. There was no significant difference between the learning outcomes of male and female students. Some male students have higher achievements because they have more engagement in science than others. Students' low ability to understand the biology concept makes them unable to perform their competency at the stages of applying, analyzing, evaluating, and creating. Overall, data showed that the average level of understanding of biological concepts for secondary school of bilingual programs still tends to be low and needs to be continuously improved in the learning process. Hopefully, further studies can be conducted to develop the most appropriate learning method to improve biological concepts.